Optimization of Cellulase Production by Aspergillus niger InaCC F506 in Solid-State Fermentation of Tofu Dreg - Talisia Kresna Shih; Agustina L. N. Aminin; Nies Suci Mulyani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Indonesia has a growing demand for cellulase enzymes; however, 99% of the enzymes are imported from other countries. Aspergillus niger is well recognized for using the widely accessible tofu by-product, often known as tofu dreg, as a growth medium for synthesizing cellulase enzymes. This study aims to optimize the production of cellulase enzymes by Aspergillus niger InaCC F506 using tofu dregs as a substrate through the Solid-State Fermentation (SSF) method by varying the additives. The results showed that the E fermentation system with the composition of urea 0.5%; CMC 0.5%; KH2PO4 0.2%; MgSO4.7H2O 0.2% produced the highest cellulase enzymes from the tofu dregs substrate. The highest cellulase enzyme activity was at a fraction of ammonium sulfate saturation level of 40-60%. The optimum condition of enzyme activity was observed at pH 5 with an activity of 33 x 10-4 Units/mg protein and at 30℃ with an activity of 31 x 10-4 Units/mg protein.